(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
In this study the influence of moisture and light on the crop value of Ledum palustre L. coenopopulations within the Rivne and Volyn regions was analyzed. The maximum resource productivity of coenopopulations of ledum is 135.8 ± 0.7 g/m2. It was found in blueberryledum- sphagnum pineries, which are characterized by a high degree of moisture (88.5 %) and low soil trophic (2.5 %) with 30 thousands lux illumination. To provide the highest output of essential oils from raw materials it should be gathered in a phase of mass flowering. Content of ledol in essential oil has the highest rates in the early fruits ripening. The highest content of tannins is in the late phase of fruiting. Found that resource and phytochemical peaks of cenopopulations of Ledum palustre L. in Rivne and Volyn regions do not match, which should be considered when planning the harvesting. The optimum conditions and terms of harvesting of raw material were defined.